Research of Performance Change Before and After in-Service Training for Relocation and Object Control Skills - Arzu Pekğöz Çeviker, Mustafa Önder Şekeroğlu (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: This study aimed to understand the effect of a customized physical education program on displacement and object control skills of classroom teachers and to compare the performance change of their skills before and after in-service training. Methods: 25 classroom teachers who participated in the research were evaluated at the beginning (pre-test) and after the four-day in-service training program (post-test). It includes the sum of the skills of running, Gallopinging, bouncing, jumping, horizontal jumping, sliding, hitting the ball with the shuttlecock, bouncing, catching, kicking the ball, throwing and rolling. Results and Conclusion: Findings from both assessment tools show that he had significantly lower coordination and skills at the beginning, and this difference changed significantly and significantly after the training program. It was concluded that the basic movement skills differed after the training. The post-in-service training shows that the displacement and object control skills of the classroom teachers increased.